ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI DASAR PENENTUAN HARGA JUAL PADA PT PAPUA KARYA JAYA - Daniel Nemba Dambe; Jasi Okta Filan (JURNAL ULET (Utility, Earning and Tax), 2022)
This study aims to analyze and calculate the cost of production of paving blocks and determine the selling price of paving blocks at PT Papua Karya Jaya. Data collection techniques in this study are observation, interview and documentation techniques. The data analysis instrument in this research uses the full costing method to calculate the cost of production and the cost plus pricing method to calculate the selling price. This research is a descriptive research. The results of this study indicate that the cost of production using the full costing method is Rp. 893,465,787 with a selling price per unit of Rp. 4,632.